INVESTMENT ANALYSIS ON THE DEVELOPMENT OF WATU ULO FISHING PORT BASED ON FINANCIAL ASPECTS AND SENSITIVITY ASPECTS - Ratuinsani, Tati Mushalihati; Muhammadun, Haris; Nugroho, Laksono Djoko (Transpublika Publisher, 2024)
Watu Ulo Beach serves as a vital hub for fishing communities, supplying resources for sea fishing and serving as a landing point for catches. The local government plans to construct a fishing port at Watu Ulo to enhance facilities for fishermen. This study assesses the financial feasibility and sensitivity of investing in the port's construction, considering three income scenarios: pessimistic, moderate, and optimistic. Financial analysis using NPV, IRR, BCR, and PP methods deems the project feasible for moderate and optimistic scenarios, but not for the pessimistic scenario due to IRR (6.15%) < MARR (7.72%). Sensitivity analysis reveals that revenue sensitivity is critical for all scenarios, with the investment becoming unfeasible if revenue falls below certain thresholds: -13.67% for pessimistic, -39.96% for moderate, and -40.75% for optimistic scenarios. Operating cost sensitivity is also crucial, rendering the investment unfeasible if costs deviate beyond specific thresholds: -15.96% for pessimistic, +22.67% for moderate, and 25.59% for optimistic scenarios.